Correlação dos sintomas gastroduodenais com o estado nutricional, consumo alimentar, esvaziamento gástrico, níveis de grelina e leptina em pacientes portadores de doença inflamatória intestinal - Sales, Kamila Maria Oliveira (2018)
Inflammatory bowel disease is characterized by delayed gastric emptying, decreased ghrelin and increased leptin. Gastroduodenal symptoms may affect nutritional status and food intake. Objective: To investigate the correlation between gastroduodenal symptoms with nutritional status, calorie and nutrient intake, gastric emptying, and serum active ghrelin and leptin levels in patients with inflammatory bowel disease. Methods: Twentyseven patients with inflammatory bowel disease (14 with Croh and 13 with ulcerative colitis), aged 18-65 years, with disease duration of approximately 11 years, were submitted to anthropometric assessment (body mass index, triceps skinfold thickness, arm circumference) and nutrient intake. (carbohydrates, proteins and lipids) at the beginning and end of the survey. In addition, patients were asked to complete the Porto Alegre Dyspeptic Symptom Questionnaire. A gastric emptying test for solids was performed using a C13 octanoic acid breath test. During the gastric emptying test, serum samples were taken to measure active concentrations of ghrelin and leptin by radioimmunoassay. Results: There was a negative correlation of most gastroduodenal symptoms with anthropometric measurements and a positive correlation with carbohydrate consumption. Patients with inflammatory bowel disease showed delayed gastric emptying being more pronounced in patients with gastroduodenal symptoms. There was a significant correlation between satiety (p = 0.0005) and vomiting (p = 0.03) symptoms with gastric emptying time. Basal leptin (p = 0.05) increased in patients with gastroduodenal symptoms compared with patients without symptoms. There were negative correlations between baseline active ghrelin and total Porto Alegre score (0.047) and epigastric pain (0.002). Conclusions: There was a negative correlation between most gastroduodenal symptoms and anthropometric measurements and a positive correlation with the consumption of Carbohydrates. Gastroduodenal symptoms correlated with disease activity and changes in gastric emptying. There was a statistically significant difference in baseline leptin in patients with gastroduodenal symptoms, and ghrelin concentrations correlated with gastroduodenal symptoms, specifically pain, which may influence the nutritional status of these patients.